Identifying tasks to elicit maximum voluntary contraction in the muscles of the forearm - Akinnola, O. O.; Vardakastani, V.; Kedgley, A. E. (Journal of Electromyography and Kinesiology, 2020)
Maximum voluntary contractions (MVCs) are often used for the normalisation of electromyography data to enable comparison of signal patterns within and between study participants. Recommendations regarding the types of tasks that are needed to collect MVCs for the muscles of the forearm have been made, specifically advocating the use of resisted moment tasks to get better estimates of forearm MVCs. However, a protocol detailing which specific tasks to employ has yet to be published. Furthermore, the effects of limb dominance on the collection of MVCs have not been considered previously. Muscle activity was monitored while 23 participants performed nine isometric, resisted tasks. The tasks that are likely to elicit MVC in the flexor carpi ulnaris, flexor carpi radialis, flexor digitorum superficialis, extensor carpi ulnaris, extensor carpi radialis, extensor digitorum communis, and pronator teres were identified. Thus, targeted protocols can be designed to mitigate against fatigue. Hand dominance had limited effect, with differences being found only in the finger flexors and extensors (p< 0.03). Thus, use of the contralateral flexor digitorum superficialis and extensor digitorum communis muscles to obtain baselines for activation levels and patterns may not be appropriate.